Monitoring of Manager and Competitive Advantage of Financial Institutions: Banks and Non-Bank - Jummaini, Jummaini; Musnadi, Said; Bachri, Naufal (JOURNAL OF ECONOMIC SCIENCE, 2015)
The purpose of this article is to know how the monitoring is conducted by the managers in improving Competitive advantage in Bank and Non-Bank institution. The independent variable consists of Policy Monitoring of Capital Structure and Blog e - CRM (Customer Relationship Management) of company. The Company value is the dependent variable, while the Competitive Advantage becomes an intervening variable. The Monitoring Information of employee is an asset for the company such as about relationship between the employee and a certain talent employee.